2022
DOI: 10.31980/mosharafa.v11i3.1486
|View full text |Cite
|
Sign up to set email alerts
|

Deskripsi Disposisi Matematis Mahasiswa pada Mata Kuliah Kalkulus 1

Abstract: Disposisi matematis adalah salah satu aspek afektif yang perlu diperhatikan dalam proses perkuliahan, sebab disposisi matematis juga dapat menunjang keberhasilan belajar dalam mengikuti perkuliahan. Penelitian ini dimaksudkan untuk mendeskripsikan disposisi matematis mahasiswa Pendidikan Matematika pada mata kuliah Kalkulus 1 di Universitas Negeri Gorontalo. Penelitian melibatkan mahasiswa pendidikan matematika yang berjumlah 47 orang. Instrumen yang digunakan adalah angket, yang didampingi dengan observasi pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…This shows that students have the confidence to be able to take basic statistics courses without any doubt, students are able to provide reasons for the statements made, students are confident that by doing a lot of assignments they will be able to master the material well. This is in line with what was found by (Machmud et al, 2022) that students who have high self-confidence believe they can do the assignment, try to answer the questions given and can put forward ideas or ideas. A similar thing was also found by (Akbar et al, 2017) that students who have self-confidence will try hard in carrying out learning activities and conversely students who lack selfconfidence do not carry out activities with all their abilities.…”
Section: Self-confidencesupporting
confidence: 91%
See 1 more Smart Citation
“…This shows that students have the confidence to be able to take basic statistics courses without any doubt, students are able to provide reasons for the statements made, students are confident that by doing a lot of assignments they will be able to master the material well. This is in line with what was found by (Machmud et al, 2022) that students who have high self-confidence believe they can do the assignment, try to answer the questions given and can put forward ideas or ideas. A similar thing was also found by (Akbar et al, 2017) that students who have self-confidence will try hard in carrying out learning activities and conversely students who lack selfconfidence do not carry out activities with all their abilities.…”
Section: Self-confidencesupporting
confidence: 91%
“…One of the affective aspects that needs to be developed is a mathematical disposition as stated by Syofyan Machmud, 2022. A positive mathematical disposition will encourage positive thinking and action (Akbar et al, 2017;Machmud et al, 2022). Mathematical disposition is a tendency to think positively about mathematics (Fatimah & Sundayana, 2022;Priatna Martadiputra, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Disposisi Matematis adalah kecenderungan untuk secara sadar (consciously), teratur (frequently), dan sukarela (voluntary) untuk berperilaku tertentu yang mengarah pada pencapaian tujuan tertentu (Machmud, Pusi, & Pauweni, 2022;Rahayu, Liddini, & Maarif, 2022).…”
Section: Berdasarkan Hasil Penelitian Timss (Trend In International M...unclassified
“…Several studies have revealed that students will tend to see mathematics as procedural rather than conceptual when it has a bad disposition (Beyers, 2011;Soesanto et al, 2020;Vukovic et al, 2013). In fact, students' sensitivity in seeing the relationship between mathematics and daily life is also influenced by the mathematical disposition they have (Beyers, 2011;Machmud, Pusi, & Pauweni, 2022). Therefore, it is very noticeable that the position of this mathematical disposition is so important in playing its role when students learn mathematics.…”
Section: Introductionmentioning
confidence: 99%